The Influence of Financial Literacy on Investment Decision Making with Herding Behavior and Loss Aversion as Moderating Variables - Dhiya mufidah erya kamila; Lisa martiah nila Puspita (CV Edujavare Publishing, 2026)
This study aims to analyze the influence of financial literacy on investment decision-making among Generation Z in Bengkulu Province, with herding behavior and loss aversion serving as moderating variables. The research employs a quantitative approach with an associative design. Data were collected through questionnaires administered to 133 Generation Z respondents who had experience investing in the capital market, and after outlier detection and data cleaning, 124 valid responses were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS version 27. The findings reveal that financial literacy has a positive and significant effect on investment decision-making, while herding behavior and loss aversion negatively moderate this relationship, indicating that higher levels of these behavioral biases weaken the positive influence of financial literacy on the quality of investment decisions. These results suggest that although financially literate investors tend to make more rational investment decisions, the effectiveness of financial knowledge may be reduced when investors are strongly influenced by the tendency to follow others or by excessive fear of potential losses. This study contributes to the development of Behavioral Finance Theory by providing empirical evidence that behavioral biases can diminish the role of financial literacy in shaping rational investment decisions among young investors. Furthermore, the findings offer practical implications for policymakers, educational institutions, and financial service providers in designing more effective financial literacy programs that not only enhance financial knowledge but also address behavioral biases, particularly among Generation Z in regional areas